Tinjauan Hukum Islam Terhadap Praktik Tabungan Sahara Ramadhan Studi Kasus Desa Siyar Kecamatan Rembang Kabupaten Pasuruan - Achmad Yasin; Saiful Bakhri; Anisak (Cashless : Journal of Sharia Finance and Banking, 2023)
The practice of Sahara Ramadhan Savings in the community of Siyar Village, Rembang District, Pasuruan Regency is unique and different compared to savings for mothers in general, because there is a different financial management system. This article uses qualitative methods and describes what was found in the field. This article attempts to describe the Sahara Ramadhan savings practice and explain it descriptively so as not to eliminate the detail and completeness of this research methodology. The results obtained from this field research are that the practice of Sahara Ramadhan savings was created because of a suggestion by one of the residents in Siyar Village, Rt/Rw 02/04, to be precise. This proposal arose because they wanted to ease the economy of mothers when they were about to enter the month of Ramadan. The conclusion from the results of this research is that if seen from the practice, it is in accordance with Islamic law. But if we look at the cuts without the members knowing, it is considered gharar and is not justified by Islamic law.